2020
DOI: 10.7150/ijms.49297
|View full text |Cite
|
Sign up to set email alerts
|

mu-Opioid Receptor Polymorphisms and Breast Cancer Recurrence in Adult Korean Women Undergoing Breast Cancer Surgery: A Retrospective Study

Abstract: Background: Genetic variations of mu-opioid receptors are well known to contribute to growth and progression of tumors. The most common single-nucleotide polymorphism (SNP) in the mu-opioid receptor 1 gene (OPRM1) is the A118G mutation. We examined the association between the recurrent breast cancer and genotypes of OPRM1 A118G SNP (AA vs. AG vs. GG) in Korean women population. Methods: We analysed medical records and genetic data of 200 patients aged m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The thermoplastic fixation makes up for the deficiencies of conventional fixation. The head mask and baseplate in the thermoplastic fixation can effectively fix the patients to make them feel comfortable and safe during treatment, and the groove and fixing lugs in the baseplate not only facilitate the fixation of headrest but also increase the comfort level [21][22][23]. Besides, Tokunaga et al [24] have pointed out that thermoplastic fixation has remarkably smaller set-up errors compared with the breast bracket and can effectively enhance radiotherapy effect and benefit the patients' prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…The thermoplastic fixation makes up for the deficiencies of conventional fixation. The head mask and baseplate in the thermoplastic fixation can effectively fix the patients to make them feel comfortable and safe during treatment, and the groove and fixing lugs in the baseplate not only facilitate the fixation of headrest but also increase the comfort level [21][22][23]. Besides, Tokunaga et al [24] have pointed out that thermoplastic fixation has remarkably smaller set-up errors compared with the breast bracket and can effectively enhance radiotherapy effect and benefit the patients' prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies have shown that inhalation anesthesia does not affect the prognosis of cancer patients after surgery. In certain types of surgery, such as digestive cancer, 101 breast cancer, 87,8995 high-grade glioma, 113 colorectal cancer, 96,99 colon cancer, 25 oral cancer, 115 and gastric cancer, 102 there was no significant difference between inhalation anesthetics and propofol in tumor patients immunity, circulating tumor cells, or survival outcomes. Consistent with these results, after anesthesia with desflurane or isoflurane in glioblastoma, the survival rate after surgery is similar, and the addition of propofol is not associated with longer survival.…”
Section: Inhalation Anesthesia and The Prognosis Of Cancer Surgery Pa...mentioning
confidence: 99%
“…(3) patients allergic to drugs involved in the study; (4) patients with long-term administration of analgesics or sedatives; (5) patients with severe anemia; (6) patients with a history of acute and chronic respiratory diseases; and (7) those in pregnancy or lactation.…”
Section: General Informationmentioning
confidence: 99%
“…Breast cancer (BC) is a type of cancer caused by the uncontrolled proliferation of mammary epithelial cells, and its incidence ranks first among female tumors worldwide [1], with 52.9% occurring in developing countries [2]. As the most populous developing country, China has the highest number of new BC patients in the world each year and the number of patients needing radical mastectomy increases yearly [3,4]. Since radical mastectomy is a body surface surgery with significant trauma and has a major impact on the respiratory system and circulatory system of patients, there is a clinical need for highly effective anesthesia modalities with good analgesic effects, such as total intravenous anesthesia [5].…”
Section: Introductionmentioning
confidence: 99%